2021
DOI: 10.1186/s12984-021-00880-w
|View full text |Cite
|
Sign up to set email alerts
|

Exoskeleton-assisted walking improves pulmonary function and walking parameters among individuals with spinal cord injury: a randomized controlled pilot study

Abstract: Background Exoskeleton-assisted walking (EAW) is expected to improve the gait of spinal cord injury (SCI) individuals. However, few studies reported the changes of pulmonary function (PF) parameters after EAW trainings. Hence, we aimed to explore the effect of EAW on PF parameters, 6-min walk test (6MWT) and lower extremity motor score (LEMS) in individuals with SCI and to compare those with conventional trainings. Methods In this prospective, sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 53 publications
1
43
0
Order By: Relevance
“…A number of bionic exoskeletons are now FDA approved for assisting walking after SCI, including Ekso TM , Rewalk TM , and Indego ® systems, as well as the implanted neuroprostheses, Parastep ® 1, which uses functional neuromuscular stimulation (FNS) to generate a majority of the muscular torque required to move and stabilize the lower extremities. These exoskeletal ambulation devices can significantly improve cardiovascular and psychological health [ 100 , 101 , 102 , 103 , 104 ]. However, unfortunately, there is no evidence to suggest that use of these devices can protect against or reverse SCI-induced bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…A number of bionic exoskeletons are now FDA approved for assisting walking after SCI, including Ekso TM , Rewalk TM , and Indego ® systems, as well as the implanted neuroprostheses, Parastep ® 1, which uses functional neuromuscular stimulation (FNS) to generate a majority of the muscular torque required to move and stabilize the lower extremities. These exoskeletal ambulation devices can significantly improve cardiovascular and psychological health [ 100 , 101 , 102 , 103 , 104 ]. However, unfortunately, there is no evidence to suggest that use of these devices can protect against or reverse SCI-induced bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…According to the physical activity guidelines, patients with SCIs should engage in at least 30 min of moderate-to vigorous-intensity aerobic exercise three times per week for cardiometabolic health benefits (Martin Ginis et al, 2018). Some studies reported that walking with WREs has numerous beneficial effects on pulmonary function (Xiang et al, 2021), bladder function (Chun et al, 2020), and sitting balance (Tsai et al, 2021). Habitual walking exercises using the WPAL three times a week for a long time may provide health benefits for patients with SCIs.…”
Section: Discussionmentioning
confidence: 99%
“…As for the sample size calculated by G*power version 3.1.9.6 (HHU, German), a pilot study [29] was performed for determinizing the effect size (1.04) of primary outcome (FVC). It was calculated that at least 16 participants were required for each group according to a significance level of 0.05 and study power of 80%.…”
Section: Sample Sizementioning
confidence: 99%